+0  
 
-2
29
2
avatar+692 

Solve for $z$ in the following equation: $2-3iz = 3 + 2z$.

 Aug 8, 2023
 #1
avatar+753 
+1

I do not know how to solve this problem, as there is i in the problem, but I'll try my best in solving it in terms of z. Firstly, I would put the two intergers together, which turns into -1 = 2z - 3iz. Then, we can turn it into 2z = -3iz - 1, and divide two from both sides. This give us z = (-3iz - 1)/2. 

 Aug 9, 2023
 #2
avatar+36746 
0

2 - 3 i z   = 3 + 2z 

-1 = 2z + 3i z 

-1 = z ( 2+3i)

-1/(2+3i) = z

 Aug 9, 2023

4 Online Users

avatar